The Hungarian Urban Network in the Beginning of the 20th Century - Beluszky, Pál; Győri, Róbert (Discussion Papers, 2012)
With the creation of the single market in the period between the “Compromise” (1867) and World War I, the integration of the formerly rather autarchic regions progressed and the urban network of Hungary was organised into a single network. The present study focuses on this latter process, the development of the urban system into an integrated network and the achievements of its process of organisa¬tion into a hierarchical system, concentrating on the conditions at the beginning of the 20th century. After presenting the historical preliminaries of the birth of the modern urban network and the conditions of urban development, the study describes the rather unbalanced urban hierarchy of the early 20th century with the weight of urban functions of Budapest largely exceeding those of other Hungarian towns. The author demonstrates the significant role of external effects in “urbanisation” such as the location of administrative institu¬tions, railway constructions, industrial development based on foreign capital etc., and concludes that the major part of the urbanisation in the Dualist era took place within the former feudal urban network, a relatively low number of “new” towns were born, yet the urban net¬work of the feudal times decreased in number. The final section provides a brief description of the respective hierarchy levels (the capital, regional centres, county seats, middle and small towns and settlements with some district level functions).